2020
DOI: 10.22271/chemi.2020.v8.i4af.10057
|View full text |Cite
|
Sign up to set email alerts
|

Available nutrients in soil are influenced by planting techniques and weed management options in wheat

Abstract: There are continue disturbance of soil under conventional wheat system as repetitive tillage practices for crop establishment results negative impact like; more weed emergence, depletion of soil nutrients and economical losses; laborious and hazardous to environment by affecting sustainability of system and creating pollution. Zero tillage practices are avoiding soil disturbance for seedbed preparation; enhance the sustainability by conserving the resources. Residue retention or application as mulching act as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…Under such condition, it is very essential to control weeds up to 45 DAS (Singh et al, 2009) [6] . Weed competition for longer period results into reduction of crop growth and yield attributes over weed free environment (Yadav et al, 2020) [19] . Herbicides offer most ideal, practical, effective and economical means of reducing early weed competition and crop production losses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under such condition, it is very essential to control weeds up to 45 DAS (Singh et al, 2009) [6] . Weed competition for longer period results into reduction of crop growth and yield attributes over weed free environment (Yadav et al, 2020) [19] . Herbicides offer most ideal, practical, effective and economical means of reducing early weed competition and crop production losses.…”
Section: Introductionmentioning
confidence: 99%
“…Melilotus spp., Solanum nigrum, Fumaria parviflora and Euphorbia spp. are the notorious weeds adversely affecting wheat crop , Verma et al, 2008, Verma, 2014and Yadav et al, 2020 [11,13,16,18,19] . Severe problem of Solanum nigrum and Physalis minima were also reported from various wheat growing parts of the country.…”
Section: Introductionmentioning
confidence: 99%
“…The total and absolute density of grassy weedswas increased up to 60 DAS and thereafter a decreasing trend was noticed, irrespective of irrigation and the herbicides application ( at 35 DAS significantly superior over weedy check but found to be least effective against these grassy weeds as compared to mix application of the herbicide treatments. Excellent control of complex weed flora in wheat was achieved with the combined (tank mix or ready mix) application of herbicides as compare to their alone application [3,17]. However, hand weedingsat 20 and 40 DAS (weed free) was found more effective than the herbicidal treatments, due to slowpace of growth of first flush of weeds at 20 days after sowing thereafter the emergence of new flushes of weeds could not attain full growth under the shade of crop plants [2,9].…”
Section: Effect On Density Of Grassy Weedsmentioning
confidence: 99%
“…It was observed that the combined application of post-emergence herbicide treatments had significant advantage over alone post-emergence herbicide and sequential herbicide treatments in controlling grassy weeds. The lowest fresh and dry weight of grassy weeds was observed with broadway (carfentrazone-ethyl 20% + sulfosulfuron 25% WG) 100 gha - [4,15,17]. None of the herbicidal treatments as effective as hand weeding at 20 and 40 DAS [11,12].…”
Section: Fresh and Dry Weighty Of Grassy Weedsmentioning
confidence: 99%
See 1 more Smart Citation